Millennial mobile payment users: A look into their personal finances and financial behavior - Carlo de Bassa Scheresberg; Andrea Hasler; Annamaria Lusardi (Asian Development Bank Institute (ADBI), 2020)
The financial technology (fintech) sector is revolutionizing traditional financial practices, yet little information exists on the users of these services. In this study, we examine untapped information from the 2015 National Financial Capability Study and the 2016 GFLEC Mobile Payment Survey to provide insights on the financial capability of American millennials who use mobile payments. Using data from both surveys, we find striking differences in financial capability between users and non-users. In particular, we reveal that users of mobile payments are more likely to overdraw their checking accounts, use credit cards expensively, borrow through alternative financial services, and withdraw from their retirement accounts. Even after controlling for socio-demographic factors, the results indicate that mobile payment users are more inclined to engage in behaviors that do not seem to follow good financial management practices.
Keywords: D14; G51; G53; G20; O16; 330; financial literacy; fintech; financial services; financial behavior; personal finance